(untitled) (London, 2003)
The book presents all the most important information about the CBD, including a guide to the decisions adopted and to the ongoing activities of the Convention. An essential reference for all the governments, intergovernmental agencies, NGOs and conservation bodies and researchers working in this area
Keywords: Biodiversity conservation; Law and legislation